2012
DOI: 10.1080/1754730x.2012.689193
|View full text |Cite
|
Sign up to set email alerts
|

Validating cultural adaptations of a school-based social-emotional learning programme for use with Latino immigrant adolescents

Abstract: Immigrant youth face many challenges as they adapt to a new culture and society. School-based social-emotional learning (SEL) interventions have been proposed to teach these children's coping skills that can help them with such life-changing transitions. A growing body of research supports the need to make adaptations to any evidence-based intervention, including SEL, to ensure the intervention's efficacy and cultural sensitivity. The purpose of this paper is to describe the process of adapting an evidence-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
46
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 28 publications
5
46
0
Order By: Relevance
“…The results of this study are aligned with those of Castro-Olivo and Merrell (2012). These find ings are important because they demonstrate that even a short intervention (12-lesson pro gram) is effective in improving ELL students' social-emotional knowledge and resiliency in ways that are acceptable and valid for them.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The results of this study are aligned with those of Castro-Olivo and Merrell (2012). These find ings are important because they demonstrate that even a short intervention (12-lesson pro gram) is effective in improving ELL students' social-emotional knowledge and resiliency in ways that are acceptable and valid for them.…”
Section: Discussionsupporting
confidence: 88%
“…For example, Tartakovsky (2007), in a study that examined the progression of acculturative stress in recent im migrant adolescents, found that acculturative stress significantly increases over a 1-year pe riod. Castro-Olivo and Merrell (2012) found that their student participants did not report a significant increase in acculturative stress over an 8-month period. Given that the current study used a simple pre-post design, the time needed to accurately assess the intervention's effect on students' acculturative stress was not available.…”
Section: Limitations and Future Directionsmentioning
confidence: 93%
See 1 more Smart Citation
“…Acculturative stress has been defined as the psychosocial stressors associated with being part of two conflicting cultures and the perceived need to conform to the host culture to avoid discrimination (Mena et al 1987). The literature suggests that acculturative stress may be a critical construct for school professionals and paraprofessionals to consider when attempting to engage in culturally responsive/competent practices in the schools (BlancoVega et al 2008;Castro-Olivo and Merrell 2012). However, the current research on acculturative stress and school-age children is limited.…”
Section: Introductionmentioning
confidence: 96%
“…More research is still needed in regard to the effects of culturally responsive practices on prevention and intervention of mental health problems like depression and anxiety in school-based settings. Several researchers who have carefully adapted their interventions to meet the specific cultural realities of their target populations within school settings, and have followed a comprehensive framework like the one proposed by Guillermo Bernal and colleagues in 1995, have noted that these practices are effective, feasible within the regular school schedule, and socially valid among their participants (Castro-Olivo and Merrell 2012;Castro-Olivo 2014;Kramer and Castro-Olivo 2016;Preciado et al 2009). …”
mentioning
confidence: 99%